KELAINAN SEKSUAL DALAM SANG GURU PIANO KARYA ELFRIEDE JELINEK DAN ODE UNTUK LEOPOLD VON SACHER–MASOCH KARYA DINAR RAHAYU Sebuah Kajian Bandingan - Linusia Marsih (Universitas 17 Agustus 1945 Surabaya, 2010)
Abstract: This thesis aims at comparing sexual disorders existed in Elfriede Jelinek’s Sang Guru Piano and Dinar Rahayu’s Ode untuk Leopold Von Sacher–Masoch. This study examines two problems: (1) the similarities and the differences of sexual disorders existed in Elfriede Jelinek’s Sang Guru Piano and Dinar Rahayu’s Ode untuk Leopold Von Sacher–Masoch and (2) psychological motivation of the main characters’ sexual disorders in Elfriede Jelinek’s Sang Guru Piano and Dinar Rahayu’s Ode untuk Leopold Von Sacher–Masoch. Descriptive qualitative method are used to analyze the texts in the two novels. The analysis shows that the main characters in each novel suffer more than one forms of sexual disorder. Comparison to sexual masochism indicates similarities to the symptoms of a person suffering masochism. The differences are the partner of each character in each novel. The motivation for the sexual disorder in each novel are family problem and personal experience factors. The study concludes that the two novels criticize inequalities faced by women in patriarchal societies and mother’s oppression on her children (Elfriede Jelinek’s Sang Guru Piano) and excessive sexual adoration of high class urban societies and disregard of moral norms and values (Dinar Rahayu’s Ode untuk Leopold Von Sacher–Masoch.) Key words: penyimpangan seksual, voyeurisme, sadisme, masokhisme, sadomasokhisme,mutilasi diri, inses, biseksual